Novel and conventional echocardiographic parameters for choosing management tactics in patients with degenerative mitral valve diseases - O. V. Tereshina; O. V. Dmitiev (Российский кардиологический журнал)
Mitral regurgitation (MR) is the second most common valvular heart disease in terms of prevalence and frequency of indications for cardiac surgery. Severe MR is characterized by a significant decrease in exercise tolerance and high mortality. The most common cause of organic MR is degenerative diseases. A detailed and systematic assessment of mitral valve and MR mechanisms is critical for the management of these patients, planning the type and timing of surgical intervention. Echocardiography plays a leading role among modern imaging methods in such patients. Examination of a patient with MR should include determining the pathogenesis of regurgitation, its severity and hemodynamic consequences. The aim of the review was to analyze the potential for using conventional and novel echocardiographic parameters to select the management strategy for patients with degenerative mitral regurgitation.